Spaces for Transdisciplinary Dialogues on the Relationship between Local Communities and Their Environment : The Case of a Rural Community in the Calchaquí Valley (Salta, Argentina) - Crivos, Marta (2016)
Our ethnographic research focuses on the perception and use of components of the natural environment in terms of routine activities carried out by the residents of a rural community in the Calchaqui Valley (Salta, Argentina). Life in this community is characterised by the presence of traditional subsistence activities – agriculture, cattle farming, textile manufacturing and ancestral medical practices – coexisting with business ventures focused on monoculture and export, tourism centred on landscape intervention and promotion of native products, and the growing key role of public policies in the areas of health and human development. In this context, a joint reflection on viability and sustainability of local and global practices and resources must be undertaken. Implementing intersectoral forums and focus-group discussions, governmental and non-governmental actors, researchers and local people must work conjointly to achieve a fresh patrimonial awareness of livelihood strategies based on their long interaction with a specific environment.